THE EFFECT OF PSYCHOLOGICAL FACTORS AND THE ORGANIZATION OF NURSE PERFORMANCE AT MITRA MEDIKA HOSPITAL - Adhisty, Ella; Situmorang, Mayasari; Febrianti, Liana (At-Tazakki: Jurnal Kajian Ilmu Pendidikan Islam dan Humaniora, 2023)
The performance of nurses must be based on a high ability to form so the performance to support the implementation of tasks in nursing services. Performance is a result of a person devoted to the task in an organization. The aim of research to determine the effect of Psychological Factors and the Organization of Nurse Performance at Mitra Medika Hospital.This research is a study that used a cross-sectional design, the samples were taken by using total population as many as 86 nurses. The collection of data taken from primary and secondary data. Analysis of the data used to determine the relationship variables using chi-square test. Measuring instrument used was a questionnaire.The results showed that most respondents have a good attitude in the category as many as 46 respondents (53.5%), motivation in both categories is 50 respondents (58.1%), in the category of no good responsiveness as many as 46 respondents (53, 5%) and reward category is not good that as many as 50 respondents (58.1%).The conclusion of this study indicate that all psychological and organizational factors influence the performance of nurses at Mitra Medika Hospital. For Mitra Medika Hospitalsuggested this study can be used as one indicator in determining policies related to efforts to improve the performance of health workers in providing care for patients.